Early childhood language and literacy development through listening skills - Umi Faizah; Anandhita, Laila; Nia Kurniasari; Lailatul Fuadah (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: Listening skills constitute the earliest form of receptive language that children acquire, serving as a foundational pillar for the development of speaking, reading, and writing. Despite their critical role, listening skills remain underrepresented in early childhood education curricula and teacher training programs. Objective: This study comprehensively examines how listening skills contribute to language and literacy development in children aged 0–6 years and identifies effective strategies for stimulating listening skills in both family and school environments. Methods: A systematic literature review (SLR) was conducted by analyzing 45 peer-reviewed articles from national and international indexed journals published between 2015 and 2024, retrieved from Google Scholar, ERIC, Scopus, and the Garuda Portal. Thematic analysis was employed to synthesize findings Results: Well-developed listening skills significantly and positively correlate with reading ability, writing proficiency, and vocabulary comprehension. Key influencing factors include the quality of parent–child interactions, the richness of the home language environment, and the quality of early childhood education programs. Interactive book reading, music and rhyme activities, and dialogic conversation were identified as the most empirically supported strategies. Conclusion: Listening skills are a critical pillar of early childhood language and literacy development, necessitating systematic attention from parents, educators, and policymakers in designing effective and sustainable language stimulation programs.